1999
DOI: 10.1021/la981553e
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Dependent Solvent Relaxation in Membranes:  Wavelength-Selective Fluorescence as a Membrane Dipstick

Abstract: Membrane penetration depth represents an important parameter which can be used to define the conformation and topology of membrane proteins and probes. We have previously characterized a set of fluorescence spectroscopic approaches, collectively referred to as wavelength-selective fluorescence, as a powerful tool to monitor microenvironments in the vicinity of reporter fluorophores embedded in the membrane. Since several membrane parameters that characterize local environments such as polarity, fluidity, segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 68 publications
6
77
0
Order By: Relevance
“…While the center of the bilayer is nearly isotropic, the upper portion, only a few angstroms away toward the membrane surface, is highly ordered. 38,[101][102][103][104][105] Properties such as polarity, fluidity, segmental motion, ability to form hydrogen bonds and extent of solvent penetration vary in a depth-dependent manner in the membrane. The interfacial region in membranes is the most important region so far as the dynamics and function of the membrane is concerned.…”
Section: Membrane Interface: An Appropriate System For the Rees Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…While the center of the bilayer is nearly isotropic, the upper portion, only a few angstroms away toward the membrane surface, is highly ordered. 38,[101][102][103][104][105] Properties such as polarity, fluidity, segmental motion, ability to form hydrogen bonds and extent of solvent penetration vary in a depth-dependent manner in the membrane. The interfacial region in membranes is the most important region so far as the dynamics and function of the membrane is concerned.…”
Section: Membrane Interface: An Appropriate System For the Rees Approachmentioning
confidence: 99%
“…38,112 It is therefore the membrane interface which is most likely to display REES. 105,[113][114][115] The application of REES to study the organization and dynamics of membranes has been reviewed recently. …”
Section: Membrane Interface: An Appropriate System For the Rees Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…1(c) shows the chemical structure of 2-AS, the fluorescent probe used. Fatty acids labeled with spectroscopic reporter groups have proved to be useful membrane probes [16]. The anthroyloxy fatty acids such as 2-AS in which an anthracene group is attached by an ester linkage to an alkyl chain have been extensively used as fluorescent probes in membranes [16,[32][33][34][35].…”
Section: Time-resolved Fluorescence Measurementsmentioning
confidence: 99%
“…This makes REES and related techniques extremely useful in biology since hydration plays a crucial modulatory role in a large number of important cellular events [7,8] such as lipid-protein interactions [9] and ion transport [10][11][12]. We have earlier shown that REES and related techniques (wavelength-selective fluorescence 459 approach) serve as a powerful tool to monitor organization and dynamics of membrane-bound probes and peptides [1,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%